ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK TERASI UDANG - PERMADI, ROKHMAN (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
The objectives of the research were to analyze the characteristics and consumers preference towards shrimp paste. Faktors and level attributes used are size (5 gr, 10gr and 25gr), presentation (burned, and have not burned), packaging (wrapper leaf, jointly and severally plastic, and aluminum foil) and purity (pure shrimp, and mixed fish). Respondents taken as many as 50 people with accidental sampling that will be required to determine the ranking of a combination of faktors and levels (stimuli) from most preferred to least preferred. Consumer characteristics were analyzed using descriptive analysis, and consumer preferences were analyzed with conjoint analysis. The results showed that the respondents prefer the paste to the size of 10gr, had been burned, the packaging wrapper leaf, and pure shrimp paste. Based on the importance rate faktor, consumers prefer packing faktor for the first, and then the purity faktor, after that the size faktor, and the last is a representation faktor.Keywords: Consumers, Preference, Shrimp Paste